Morphological analysis of the omovertebral bone and scapula in children with sprengel deformity using three-dimensional computed tomography - Li, Tao; Meng, Jiajing; Lei, Yinghan; Jiang, Hai (Frontiers in Pediatrics, 2025)
ObjectiveSprengel deformity represents a rare complex congenital anomaly in children, characterized by malposition and dysplasia of the scapula. The omovertebral bone is considered to be the key pathoanatomic structure that affects the scapula and prevents its normal descent. Three-dimensional computed tomography (3D-CT) was employed in this study to clarify the morphological abnormalities of both the omovertebral bone and the scapula, thereby enhancing our understanding of this uncommon condition.MethodsFrom January 2,012 to June 2024, we enrolled 12 children (6 males and 6 females; mean age 4 years, range 2–7) with Sprengel deformity, confirmed by imaging to possess an omovertebral bone. Preoperative CT scans with 3D reconstruction were performed on all patients. We assessed the spatial location and morphology of the omovertebral bone in each case and quantified the following parameters: the height-to-width ratio of both scapulae, the extent of superior displacement of the affected scapula, and its 3D-CT rotational divergence (angle of tilt) compared to the contralateral side.ResultsBased on the Cavendish grading system, 2 shoulders were classified as grade 2, and 10 were grade 3. According to the Rigault classification, 7 shoulders were grade 2, and 5 were grade 3. The mean height-to-width ratio of the affected scapulae was significantly reduced compared to the contralateral side. The infraspinous portion of the vertebral border exhibited convexity in 11 out of 12 cases, and all affected scapulae demonstrated rotational deformity. The omovertebral bone is most frequently connected to the cervical spine at C6. Its scapular attachment site was infraspinous along the vertebral border in 9 children and mesoscapular in 3. The omovertebral bones displayed diverse morphologies, predominantly irregular in shape.ConclusionBy precisely delineating the diverse morphology and spatial location of the omovertebral bone and the complex scapular distortion in three dimensions, 3D-CT provides invaluable pathoanatomic data that significantly advance our understanding of Sprengel deformity in children.Level of EvidenceLevel IV—observational study design.